2018
DOI: 10.1111/bjh.15452
|View full text |Cite
|
Sign up to set email alerts
|

An unbalanced monocyte macrophage polarization in the bone marrow microenvironment of patients with poor graft function after allogeneic haematopoietic stem cell transplantation

Abstract: Poor graft function (PGF) is a severe complication of allogeneic haematopoietic stem cell transplantation (allo-HSCT). Murine studies have demonstrated that effective haematopoiesis depends on the specific bone marrow (BM) microenvironment. Increasing evidence shows that BM macrophages (MФs), which constitute an important component of BM immune microenvironment, are indispensable for the regulation of haematopoietic stem cells (HSCs) in the BM. However, little is known about the number and function of BM MФs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
(75 reference statements)
0
36
0
Order By: Relevance
“… 57 59 A recent case-control study revealed a significant increase in M1 (classically activated inflammatory macrophages) and a striking reduction in M2 (alternatively activated anti-inflammatory macrophages) in PGF patients compared with those with GGF. 60 The functions of BM macrophages, such as proliferation, migration, and phagocytosis, were impaired in PGF patients. Moreover, when cocultured with BM macrophages from PGF patients, the function of CD34 + cells was impaired through the upregulation of the p38 MAPK pathway.…”
Section: The Mechanismmentioning
confidence: 99%
“… 57 59 A recent case-control study revealed a significant increase in M1 (classically activated inflammatory macrophages) and a striking reduction in M2 (alternatively activated anti-inflammatory macrophages) in PGF patients compared with those with GGF. 60 The functions of BM macrophages, such as proliferation, migration, and phagocytosis, were impaired in PGF patients. Moreover, when cocultured with BM macrophages from PGF patients, the function of CD34 + cells was impaired through the upregulation of the p38 MAPK pathway.…”
Section: The Mechanismmentioning
confidence: 99%
“…As a selective Janus kinase (JAK) 1/2 inhibitor, ruxolitinib blocks T cell activation and survival, while also influencing the differentiation and mutation of dendritic cells (Bendstrup et al , ). Pirfernidone is used in idiopathic pulmonary fibrosis (Du et al , ), and is also effective in murine models of sclerodermatous cGVHD, as it inhibits macrophage infiltration and TGF‐ production (Zhao et al , ), while macrophage reconstitution is very important to haematopoietic microenvironment and development of GVHD after transplantation. Low‐dose subcutaneous IL2 is another strategy for corticoid‐refractory cGVHD due to its crucial role in augmenting Treg expansion, survival and activity (Koreth et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages can be referred to as either classical macrophages (M1) or alternative macrophages (M2) [35,36]. As previously reported [21,22] for analysis of M1 and M2, BMMNCs were stained with anti-CD14-PE, anti-CD68-FITC, anti-CCR2-BV421, anti-CX3CR1-PerCP/ Cy5.5 and anti-CD163-PE/Cy7 (BioLegend, San Diego, CA, USA). M1 and M2 were identified as CD14 + CCR2 + CD68 + and CD14 + CX3CR1 + CD163 + , respectively.…”
Section: Analysis Of Macrophage Subsetsmentioning
confidence: 99%
“…Moreover, aGVHD is generally considered to be associated with increased percentages of donor T helper-1 (Th1) and T cytotoxic-1 (Tc1) cells and decreased percentages of T helper-2 (Th2) and T cytotoxic-2 (Tc2) cells [16][17][18][19]. Macrophages were involved in aGVHD, poor graft function and some other complications post allo-HSCT [20][21][22][23]. However, little is known about the differences in the percentages of cytokine-producing T cell subsets and macrophage subsets in BM between young and older donors.…”
Section: Introductionmentioning
confidence: 99%